23. International Biennial of Graphic Art Ljubljana. - Galerija Tivoli, Ljubljana; Moderna galerija, Ljubljana; Jakopiceva galerija, Ljubljana; Andreassen, Astrid V.; Bonomi, Maria; Boulanger, Sylvie; Choi, Tae-Man; Devon, Marjorie; Feinsilber, Laura; Ficacci, Luigi; Fogelberg, Ann-Christine; Garff, Jan; et al. (Ljubljana: International centre of graphic arts, 1999)
Lecuona, Juan ; Marin, Matilde ; Pereda, Teresa ; Weil, Tiny ; Bowen, Dean ; Boag, Yvonne ; Raymond, Arnold ; Fransella, Graham ; Namok, Rosella ; Sheppard, Margie ; Josef, Dieter ; Maltrovsky-Haider, Johannes ; Schneider, Michael ; Schlegel, Eva ; Sauer, Birgit ; Vavra, Inge ; Lenoir, Thiery ; Kamenov, Zahari ; Karamfilov, Kolyo ; Lechev, Georgi ; Mirazchiev, Emil ; Popov, Vassil ; Bojkov, Stefan ; Sevova, Dimitrina ; Barros, J. ; Monforte, Luiz ; Bartira, Uiara ; Khoury, Feres ; Mubarac, Claudio ; Axmann, Mikolás ; Vicar, Jan ; Kucerova, Alena ; Cepelak, Ladislav ; Kruse, Tune ; Sorensen, Bjarne Werner ; Siib, Liina ; Tali, Andres ; Laimre, Marko ; Hautala, Jorma ; Mikkonen, Tapani ; Hanhijoki, Marjatta ; Morellet, François ; Sutej, Miroslav ; O'Malley, Tony ; Pomodoro, Arnaldo ; Arienti, Stefano ; Canevari, Paolo ; Carolrama, Carol Rama - ; Strazza, Guido ; Watabiki, Akihiro ; Marino, Mayumi ; Kobayashi, Keisei ; Takeda, Fumiko ; Nagashima, Mitsuru ; Knezevic, Slobodan ; Pavic, Branko ; Todovic, Zoran ; Besant, Derek ; Chiba, Taiga ; Levytsky, Ina ; May, Margaret ; Pelletier, Louis ; Peck, Robin Smith ; Yamamoto, Koichi ; Templeton, Tracy ; Zurakowska, Malgorzata ; Zeigler, Barbara ; Smith, Joan ; Sun, Jung Hwan ; Jun, Hyun Joe ; Kim, Bong Tae ; Kim, Young Sik ; Park, Jeong Ho ; Kim, Sun ; Song Dae-Sup ; Nagy, Gábor György ; Gaal, Jozsef ; Tolnay, Imre ; Lévay, Jenö ; Haasz, Agnes ; Hanske, Andreas ; Schwarz, Linda ; Novaky, Akos ; Vetter, Ulrike ; Hoffmann, Bogdan ; Furtwängler, Felix M. ; Minkewitz, Reinhard ; Hagen, Inger ; Maehlum, Ellen Karin ; Torseter, Oivind ; Piotrowski, Krystyna ; Jaromski, Marek ; Szurek, Piotr ; Zawadzka, Ewa ; Rivera, Martin Gracias ; Kunhardt, Susana Herrero ; Cierna, Pavlina Fichta ; Csudai, Ivan ; Havrilla, Vladimir ; etc.
23. International Biennial of Graphic Art Ljubljana, Galerija Tivoli / Moderna galerija / Jakopiceva galerija / Cankarjev dom, Ljubljana, 29. junij - 30. september 1999
Engels
boek
Keywords: Joegoslavië; Ljubljana